1995
DOI: 10.1111/j.2044-8279.1995.tb01130.x
|View full text |Cite
|
Sign up to set email alerts
|

A structural model of the dimensions of teacher stress

Abstract: A comprehensive survey of teacher stress, job satisfaction and career commitment among 710 full‐time primary school teachers was undertaken by Borg, Riding & Falzon (1991) in the Mediterranean islands of Malta and Gozo. A principal components analysis of a 20‐item sources of teacher stress inventory had suggested four distinct dimensions which were labelled: Pupil Misbehaviour, Time/Resource Difficulties, Professional Recognition Needs, and Poor Relationships, respectively. To check on the validity of the Borg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
234
1
16

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(254 citation statements)
references
References 73 publications
(88 reference statements)
3
234
1
16
Order By: Relevance
“…In comparison with other occupations, teaching has been consistently ranked as a high-stress job (JOHNSON et al 2005;TRAVERS & COOPER 1996), with 33-37% of teachers frequently reporting being very or extremely stressed as a result of factors intrinsic to their work (BOYLE et al 1995;CHAN & HUI 1995;KYRIACOU 2001). Many studies in several countries have focused on the determinants and consequences of teacher stress (BENMANSOUR 1998;BYRNE 1999;CHAN & HUI 1995;DUNHAM & VARMA 1998) and also in Italy (CAVALLI 2000) teaching has been confi rmed as a 'high-stress occupation'.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with other occupations, teaching has been consistently ranked as a high-stress job (JOHNSON et al 2005;TRAVERS & COOPER 1996), with 33-37% of teachers frequently reporting being very or extremely stressed as a result of factors intrinsic to their work (BOYLE et al 1995;CHAN & HUI 1995;KYRIACOU 2001). Many studies in several countries have focused on the determinants and consequences of teacher stress (BENMANSOUR 1998;BYRNE 1999;CHAN & HUI 1995;DUNHAM & VARMA 1998) and also in Italy (CAVALLI 2000) teaching has been confi rmed as a 'high-stress occupation'.…”
Section: Introductionmentioning
confidence: 99%
“…This study suggests that a program that focuses on a particular subgroup (e.g., those with high stress responses or high job control) might be effective seven years 14) . Previous studies [15][16][17][18] have revealed several problem areas for teachers, such as poor school environment, student misbehavior, poor working conditions, personal concerns, relationships with pupils' parents, time pressure, or inadequacy of training. In almost all studies, student misbehavior was consistently identified as the most stressful problem 18) .…”
mentioning
confidence: 99%
“…Li te ra tür de de benzer so nuç la ra ula şıl mış tır. 18,27,28 Ge lir so run la rı ve tü ken miş lik alt öl çüm le rinden duy gu sal tü ken miş lik ara sın da an lam lı iliş ki ler sap tan mış tır. Tür ki ye ko şul la rın da öğ ret men maaş la rı çok ye ter siz dir ve tüm eği tim ka de me le rinde gö rev ya pan öğ ret men ler ge çim so run la rı ya şa mak ta dır lar.…”
Section: Tar Tiş Maunclassified